PRAKTIK MANAJEMEN RANTAI PASOK DAN TEKNOLOGI BISNIS BERBASIS ELEKTRONIK SEBAGAI PEMODERASI PERUSAHAAN MANUFAKTUR - Magdalena Wullur; Wardaya Wardaya (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2015)
This research develops and tests the consistencies of the relation between supply chain management practices, e-business technologies and operational performance. The data for this research is obtained from 67 companies. The relations proposed in the framework of this research are tested using partial least square analysis. The findings of this research shows the impact of supply chain management practices and e-business technologies have an effect on improvement of operational performance. The analysis also found the existence of interaction effect between SCM practices and e-business technologies, both on operational performance.